Body stalk anomaly: Three months of survival. Case report and literature review - Thiago Luiz Do Nascimento Lazaroni; Paulo Custódio Furtado Cruzeiro; Clécio Piçarro; Átila Magalhães Victoria; Fábio Mendes Botelho Filho; Edson Samesima Tatsuo; Marcelo Eller Miranda (Elsevier, 2016)
Body stalk anomaly is composed of a set of genetic component abnormalities that are still rather unknown. This anomaly consists of a large defect in the abdominal wall closure, anatomical defects of the pelvis and lower limbs, severe scoliosis, and pulmonary hypoplasia. In addition to these deformities are heart disease and neural tube closure defects. Because of the association of these severe deformities, the cases described in the literature have proven to be almost entirely incompatible with life, resulting in abortion and stillborn fetuses. Therefore, the present article describes a case of body stalk anomaly that survived for nearly three months, the first of its kind in Latin America.